1981
DOI: 10.1017/s0022112081001390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rotation on the stability of a doubly diffusive fluid layer

Abstract: The stability of a rotating doubly diffusive fluid is considered. It is shown that (1) a non-rotating layer can be destabilized by rotation, (2) a rotating layer can be destabilized by the addition of a bottom-heavy solute gradient, and (3) under some conditions, three thermal Rayleigh numbers are required to specify linear stability criteria. Numerical results are presented on the basis of which the explanation by Acheson (1979) of the second of these three anomalies can be assessed, and Acheson's explanation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0
2

Year Published

1986
1986
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 32 publications
(17 reference statements)
6
36
0
2
Order By: Relevance
“…In linear stability analysis, it has been found that the rotation inhibits the onset of convective instability (Pearlstein, 1981). When the rotation strongly affects DC, the onset Rayleigh number, Ra c , would be in the form of…”
Section: The Classical Description Of DC Instabilitymentioning
confidence: 99%
“…In linear stability analysis, it has been found that the rotation inhibits the onset of convective instability (Pearlstein, 1981). When the rotation strongly affects DC, the onset Rayleigh number, Ra c , would be in the form of…”
Section: The Classical Description Of DC Instabilitymentioning
confidence: 99%
“…There are several studies available in which phenomena related to the onset of convection in a rotating porous medium have been investigated. Few of them are: Pearlstein (1981), Chakrabarti and Gupta (1981), Patil and Vaidyanathan (1983) Patil et al (1990), Qin and Kaloni (1995), Vadasz (1998), Desaive et al (2002), Govender (2006Govender ( , 2008, Maharaj and Saneshan (2005), Riahi (2005). Bhadauria (2007bBhadauria ( ,c, 2008a, Bhadauria and Suthar (2008b), and Vanishree and Siddheshwar (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Few of them are Perlstein [6], Chakrabarti and Gupta [7], Patil and Vidyanathan [8], Vadasz [9]. Convection in porous medium has been studied by many authors including Horton and Roger [10], Lapwood [11], Nield [12], Rudraiah and Malshetty [13], Murray and Chen [14], Bhadauria [15], Vafai [16], Neild and Bejan [17].…”
Section: Introductionmentioning
confidence: 99%